XXYLT1 methylation contributes to the occurrence of lung adenocarcinoma: Methylation and lung adenocarcinoma. Issue 1 (8th January 2021) - Zeng, Hui; Wang, Ying; Wang, Ying; Zhang, Yongjun
Abstract: Background: There is evidence that DNA methylation play major roles in lung cancer. In our previously study, C3 or f21, also referred to as XXYLT1, rs2131877 polymorphism is associated with a reduced risk of lung adenocarcinoma. So, we explored the role of XXYLT1 methylation in lung adenocarcinoma. Methods: This study was conducted in 2 steps. In the first step, we recruited 15 patients with lung adenocarcinoma. Cancer tissues and para-carcinoma tissues were obtained from each of the patients. In the second step, 150 patients with lung adenocarcinom were enrolled, and cancer and normal lung tissue were obtained from each patients, respectively. The expression levels of XXYLT1 mRNA were determined, the deoxyribonucleic acid methylation status was analyzed by MassARRAY Spectrometry. The methylation data of individual units were generated by EpiTyper v1.0.5 software. Results: The XXYLT1 mRNA expression was significantly lower in cancer tissues than in para-carcinoma and normal lung tissues. Meanwhile, the methylation rates of three CpG units (CpG_23, CpG_25, and CpG_60.61.62.63.64.65) within the XXYLT1 gene were higher in cancer tissues compared to the para-carcinoma and the normal lung tissues. This difference was particularly significant in male patients. Conclusions: Our results suggested that methylation of XXYLT1 may have significance in the pathogenesis of lung adenocarcinoma.